Áp dụng lý thuyết hành vi dự định để giải thích hành vi giảm lãng phí thực phẩm của người tiêu dùng Việt Nam: Vai trò của nhận diện xanh - Đặng Hoàng Thái, Hiền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This research integrates the concept of green identity, which operates as self-identification based on environmental values and sustainable behaviors, into an extended model of the theory of planned behavior in the context of food consumption at restaurants. Green self-identity is examined both as a direct factor and as a moderator in the relationships among TPB components to explain the intention to reduce food waste. The PLS-SEM method is employed to test the research model and evaluate the hypotheses. The results indicate that attitude, perceived behavioral control, and subjective norms all positively influence the intention to reduce food waste. Notably, green self-identity not only has a direct effect but also moderates the interrelationships among the TPB components, highlighting its importance in promoting the intention to reduce food waste in restaurant settings. Therefore, this study provides empirical evidence on the role of green self-identity as an aspect of personal identity that contributes to the formation of behavioral intentions to reduce food waste, while also laying the foundation for effective interventions in order to reduce food waste at restaurants.